2011
DOI: 10.17221/1556-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The spinal nerves that constitute the brachial plexus in the red squirrel (Sciurus vulgaris)

Abstract: ABSTRACT:The brachial plexus in adult red squirrels (Sciurus vulgaris) was found to be formed by the rami ventralis of C5, C6, C7, C8. A thin branch of C5 and C6 constituted the cranial trunk, and the caudal trunk was formed completely by the rami ventralis of C7 and C8. Thus, in squirrels, the spinal nerves which form the brachial plexus and the joining of these spinal nerves to each other differ from other rodents and mammals.Keywords: spinal nerves; rami ventralis; brachial plexus; red squirrels List of abb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
12
0
7
Order By: Relevance
“…The constitution of the brachial plexus of molerats (Spalax leucodon) by one trunk differs from the situation in the rat (Bertelli et al 1992), and Chacma baboon (Booth et al 1997), where it is formed by the caudal, medial and cranial trunks, and from the situation in rabbits (Yilmaz et al 1995), porcupines (Aydin 2003) and squirrels (Aydin 2011) where it is formed from caudal and cranial trunks.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The constitution of the brachial plexus of molerats (Spalax leucodon) by one trunk differs from the situation in the rat (Bertelli et al 1992), and Chacma baboon (Booth et al 1997), where it is formed by the caudal, medial and cranial trunks, and from the situation in rabbits (Yilmaz et al 1995), porcupines (Aydin 2003) and squirrels (Aydin 2011) where it is formed from caudal and cranial trunks.…”
Section: Discussionmentioning
confidence: 96%
“…Yilmaz et al (1995) reported that the brachial plexus of the rabbit is formed by the ventral rami of C5, C6, C7, C8, T1 and T2, while Aslan (1994) and McLaughlin and Chiasson (1987) rejected the contribution of C5 and T2. The brachial plexus is formed by the ventral rami of C5, C6, C7, C8 and T1 in mice (Cook 1965;Bogusch 1987), by the ventral rami of C5, C6, C7 and C8 in squirrels (Aydin 2011), by the rami ventralis of C5, C6, C7, C8, T1 and T2 in Wervet monkeys (Booth 1991),in Chacma baboons (Booth et al 1997) and in porcupines (Aydin 2003) and the ventral rami of C6, C7, C8 and T1 in cats (McClure et al 1973;Getty 1975). Tipirdamaz and Erden (1988) and Dursun et al (1994) reported that in dogs the brachial plexus is formed by the ventral rami of C6, C7, C8, T1 and T2, while Miller et al (1964) and Getty (1975) reported that T2 is involved occasionally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suprascapular nerves innervate the supraspinatus, and infraspinatus muscles (Table 3). Aydin (2011) reported that the axillary nerve in the red squirrel originates from C 5 -C 6 , whereas in the paca (Scavone et al 2008), coypu (Guimaraes et al 2013), chinchilla (Gamba et al 2007), and rat (Greene 1963), it is formed from C 6 and C 7 , similarly to the Spix's yellow-toothed cavy. According to Guimaraes et al (2013), in the coypu, branches towards the deltoid teres major, teres minor and subscapularis muscles are observed, as is the case in the Spix's yellow-toothed cavy.…”
Section: Mazama Gouazoubiramentioning
confidence: 99%
“…Com origem predominante em C6 e C7 (70%) no C. thous, o nervo supra--escapular foi formado de modo semelhante no cão domés-tico (Allam et al 1952, Ghoshal 1986b, nos equinos, nos ruminantes domésticos (Magilton et al 1968), em Arctocephalus australis (Souza et al 2010) e em Atelocynus microtis (Pinheiro et al 2013). Originou-se de C5 e C6 em Papio ursinus (Booth et al 1997), em Lagothrix lagothricha (Cruz & Adami 2010), em Pan paniscus (Kikushi et al 2011), em Sciurus vulgaris (Aydin 2011), em Tamandua tetradactyla (Cruz et al 2012) e em Hippopotamus amphibius , de C5, C6 e C7 nos suínos (Magilton et al 1968) e em Agouti paca (Scavone et al 2008), de C4, C5, C6 e C7 em Hydrochaeris hydrochaeris (Fioretto et al 2003) e em Tayassu tajacu (Moura et al 2007), de C6, C7 e C8 em fetos de bovinos azebuados ) e apenas de C6 nos felinos domésticos (Ghoshal 1986b), alguns caprinos (Ghoshal 1986a) e em Chinchilla lanigera (Gamba et al 2007). Estudos eletrofisiológicos em seis cães domésticos revelaram que o n. supra-escapular recebeu potenciais evocados dos ramos ventrais de C6 e C7 em todos os animais avaliados (Sharp et al 1991), o que reforça a importância funcional destes ramos para o nervo em canídeos.…”
Section: Quanto à Distribuição Dos Nervos Do Plexo Braquialunclassified